The Effect of Subinhibitory Concentrations of Ciprofloxacin on Reca Expression and Mutation Rates of Aeromonas Hydrophila - (:unkn) unknown (My University, 2021)
Despite antibiotic resistance threatening global health, consumption of antibiotics continues to rise. With human and agricultural overuse and improper disposal, antibiotics are found throughout aquatic environmental sources. These environmental contaminants can behave as microbial stressors inducing survival pathways as a prelude to increased mutation rates and subsequent antibiotic resistance. The bacterial SOS response is one such survival pathway, the mutational activity of which is induced by the expression of the activator RecA in response to cell stress. The activity of RecA is largely undefined in Aeromonas hydrophila, a human pathogen ubiquitous in waterways. In the present study, our objective was to determine the direct effect of RecA on mutagenesis in response to incubation with subinhibitory concentrations of ciprofloxacin. First, we determined the expression of recA in response to exposure to sub-MIC levels of ciprofloxacin using real-time PCR. We found increased expression of recA consistent with induction of the SOS response. Then we developed a recA deletion using splicing by overlap extension PCR. Briefly we amplified fragments flanking recA with complementary overhangs, ligated the fused fragments on suicide vector pEX18Tc and inserted this via transformation to an intermediate Escherichia coli strain, S17-1. The modified vector plasmid was acquired in A. hydrophila ATCC 7966 via filter mating. Subsequent homologous recombination transferred the wild type recA onto the suicide plasmid leaving recA absent on the chromosome. Post-conjugation, high sucrose media counter-selected for strains without the plasmid leaving either wild type or deletions. After PCR screening of all resulting colonies and confirmation of a deletion, we analyzed the effect of sub-inhibitory concentrations of ciprofloxacin on mutation rate amongst the wild type and recA knock out A. hydrophila. Exposure to half the minimum inhibitory concentration of ciprofloxacin resulted in a statistically significant tenfold increase (p